The Effect of Inhibitor Frequency on the Anemia Status of Junior High School Girls in Batu Bara District - Aci Debby Nasution; Etti Sudaryati; Zulhaida Lubis (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
To this day, anemia is still a nutritional problem, especially indeveloping countries, including Indonesia. One of the groups most susceptible to anemia is adolescent girls, because adolescent girls menstruate as a physiological condition of a woman. Based on the results of preliminary survey data, 30 adolescent girls were found to have anemia.where more junior high school or MTS girls are found to be anemic18 people. From the results of preliminary interviews with 15 anemic female students, 46.7 percent, or 7 female students, often consume coffee, or 93.3 percent.or 14 female students often consume tea, and 93.3 percent, or 7 female students often consume tea and coffee. This study used a survey methodology with a case-control design. The research was conducted in junior high schools in Batu Bara District in October-December 2023. This study aims to examine the impact of inhibitor intake on the prevalence of adolescent anemia in the Batu Bara district. The study included a total of 120 samples, consisting of 30 cases and 90 controls, with a ratio of 1:3. The study found no significant correlation between the frequency of inhibitor consumption and the occurrence of anemia in teenage girls attending junior high school girls in the Batu Bara region (OR= 0,571, 95% CI 0,241-1,357). It is necessary to study the amount of iron, protein, and vitamin C, vitamin B12 intake, and morning absorption habits so that the researchers can dig deeper and be more detailed about the quantity of food intake associated with the occurrence of anemia. Keywords : Anemia, inhibitor, junior high school